Hallowed Grounds - Helge Årsheim (Temenos)
This article examines the identification and protection of the sacred natural sites (SNS) of Indigenous peoples, with a particular emphasis on a selection of cases where the Sámi people’s SNS have come under pressure in Sápmi. The article unpacks the origins and impact of the concept of SNS, from the international level to domestic decision making. A key concern of this investigation is how discourses on SNS have come to interact with and influence other issues of global governance, from environmental and biological diversity concerns and activism for cultural heritage to protective measures for the human rights of Indigenous peoples. Following this overview, the article discusses the extent to which the Norwegian authorities, commercial actors, and civil society activists have drawn on the international SNS discourse to formulate their claims in a series of cases concerning energy developments in Sápmi.